Distance from a cultural model of substance use risk, internalization, and self-stigma in urban Brazil - Henderson, Nicole L.; Dressler, William W.; Pegoraro, Natália Priolli Jora; Falcão, Ana; Pillon, Sandra Cristin (Frontiers in Psychology, 2023)
Introduction A cognitive theory of culture as socially distributed cultural models has proven useful in research. Cultural models exist in two forms: the model shared by individuals in a social group, and individual versions of that model modified by personal experience. In previous research we documented a shared cultural model of substance use risk among a general population sample in urban Brazil. Here we examine how this model is distributed among persons under treatment for substance use/misuse and the implications for perceived and self-stigma. Methods A convenience sample of 133 persons under treatment rated the influence of risk factors for substance use/misuse. The configuration of those ratings and the cultural distance of persons under treatment from the general population model were calculated. Degree of stigma perceived in the wider society and degree of self-stigma were also assessed. Results Persons under treatment aggregate risk factors to a greater extent than the general population. Using a cultural distance metric, the more distant persons under treatment are from the general population model, the lower their self-stigma regarding substance use. Discussion Some individuals under treatment separate their understanding of substance use/misuse from shared perspectives in the wider society, which in turn reduces self-stigma. These findings add an additional perspective on the relationship of culture and the individual.